INFLUENCE OF DIFFERENT EXTRAJOSS CONCENTRATIONS OF GRANTING ON MEDIA CULTURE AGAINST THE RATE OF POPULATION GROWTH OF ROTIFER (B. plicatilis) - Raja Yogi Prayoga; Syafruddin Nasution; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in October to December 2016 at fish seed center Pengujan, Bintan, Riau Island. The purpose of research was to determine the best concentration of Extrajoss for improving the rate of population growth of B. plicatilis in media culture. Complete Random Design (CRD) was applied as a method at this study with 4 taraf treatments that is P0 media consists of 300 mg chicken manure, 7.5 mg TSP, 6 mg Urea, 0.45 g yeast Bread/3 liters of water (control), then for further media added P1 (0.30 g Extrajoss), P2 (0.40 g Extrajoss), and P3 (0.50 g Extrajoss) with 3 replicates and observation 2 times day. The results is there’s a population growth rate differences occurring B. plicatilis after being given by Extrajoss. The highest population density is obtained at the 6th day of observation in the media of P2 11.36 ind/ml, and the lowest population contained on media P3 Of 1.00 ind/ml, while the highest average growth rate was obtained at the treatment the P2 of 2.731 ind/ml and the lowest obtained on treatment of P3 of 1.257 ind/ml.Keywords: Brachionus plicatilis, Extrajoss, BBI Pengujan